Quantum Information and Symmetry - Leonski, Wiesław; Kalaga, Joanna K.; Szczęśniak, Radosław (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Recent research in the fields related to the quantum information theory (QIT) is becoming some of the most intriguing and promising investigations in contemporary physics. Many novel QIT concepts are discussed in the literature, and the broad range of new models of quantum optics and solid-state physics have been recently considered in the context of QIT. Theideas of symmetry are widely discussed in all physical sciences, becoming keystones of various concepts and considerations, leading to novel discoveries in physics. Thus, this Special Issue is devoted to the broad range of QIT topics that are related to the ideas of symmetry. It covers a broad range of ideas that can develop upon the basic research and applications in the field of quantum information, and in general, quantum theory.